The pulsed dye laser is more effective and rapidly acting than intralesional meglumine antimoniate therapy for cutaneous leishmaniasis. (4th July 2017) - Radmanesh, Mohammad; Omidian, Ehsan
Abstract: Background and objective: The pulsed dye laser (PDL) is not tested yet for the treatment of cutaneous leishmaniasis (CL). We compared the efficacy of 585 nm PDL with intralesional meglumine antimoniate (MA) on 17 patients with 81 lesions of CL. Patients and methods: Out of the 81 lesions, 42 lesions were treated with one or two passes of PDL fortnightly and 39 lesions in the same patients were treated with intralesional MA weekly. The fluence chosen for the laser was 7 Joules/cm² with 5 mm spot size. The MA treated lesions were infiltrated gently with MA to blanch the lesions completely. Results: All laser treated lesions were responded well with almost 66.7% cure after the first, and more than 90% after the second treatment. One patient was recovered after third, and the last one after fourth sessions. All 39 MA treated lesions were also responded after third to eighth sessions. The mean number of the sessions required for the patients to be treated with PDL is 1.85, and the mean number of the sessions required for the patients to be treated with MA is 4.6. Conclusions: The PDL can cure many cases of CL particularly in their early stages faster than MA.